Analisis Pengaruh Kualitas Situs Web Kampus Merdeka terhadap Kepuasan Pengguna dengan Metode WebQual 4.0 (Studi Kasus: Mahasiswa SVI) - Rona Nisrina Rahmawati; Intan Sartika Eris Maghfiroh; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
After the COVID-19 pandemic, the government continues to pay close attention to study plans, one of which is implemented in universities, namely Merdeka Belajar Kampus Merdeka (MBKM). In order to support the implementation of activities, the government to create an official website for the Kampus Merdeka (KM). In its development, the quality of the website becomes an important part that needs attention. This research was conducted to get feedback from students, especially the internship program at Skilvul Virtual Internship. WebQual 4.0 method is related to measuring the influence of website quality on user satisfaction. Data was collected through the distribution of online questionnaires containing as many as 20 statement items from all the variables used. Using purposive sampling technique got a total of 106 respondents with valid answers. Data analysis using multiple linear regression with the SPSS 26 program resulted showing the three WebQual 4.0 variables simultaneously affecting 80.1% of user satisfaction variables, while the rest was explained by factors other than those in the study. Meanwhile, the partial test results show that the usability quality variable has no significant effect compared to the other two variables, namely the information quality variable and the service interaction quality which have a significant and positive effect on the user satisfaction variable on the KM website.